Respostas
respondido por:
1
Explicação passo-a-passo:
a) 3+×=0
×= -3
b) 23×+2=2
23×= 2-2
23×= 0
×= 0/23
×= 0
c) 12-7+4×=25
4×= 25 +7 - 12
4×= 20
×= 20/4
×= 5
d) 5×-3×=30
2×=30
×= 30/2
×= 15
e ) 4×+10=45-3×
4×+3×= 45 -10
7×= 35
×= 35/7
×= 5
2)
a) ×-3= 9
×= 9/3
×= 3
b) 4×-9= 1-2×
4×+2×= 1+9
6×= 10
×= 10/6 reduz por 2
×= 5/3
c) ×+5=20-4×
×+4×=20-5
5×=15
×=15/5
×= 3
d) 9×-4×+10=7×-30
5×-7×=10-30
-2×=-20 (-1)
×= 20/2
×= 10
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás